2004
DOI: 10.1091/mbc.e04-03-0253
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Interchromatin Granule Clusters

Abstract: A variety of proteins involved in gene expression have been localized within mammalian cell nuclei in a speckled distribution that predominantly corresponds to interchromatin granule clusters (IGCs). We have applied a mass spectrometry strategy to identify the protein composition of this nuclear organelle purified from mouse liver nuclei. Using this approach, we have identified 146 proteins, many of which had already been shown to be localized to IGCs, or their functions are common to other already identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
294
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(313 citation statements)
references
References 73 publications
16
294
2
1
Order By: Relevance
“…The RD/E dipeptide motif is similar to a phosphorylated RS domain, because the serine residue in the RS repeat is replaced with a negatively charged aspartic acid or glutamic acid residue. Consistent with this observation, the CF I m 68-kDa subunit was identified as a component of isolated IGCs (Saitoh et al, 2004).…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…The RD/E dipeptide motif is similar to a phosphorylated RS domain, because the serine residue in the RS repeat is replaced with a negatively charged aspartic acid or glutamic acid residue. Consistent with this observation, the CF I m 68-kDa subunit was identified as a component of isolated IGCs (Saitoh et al, 2004).…”
Section: Introductionsupporting
confidence: 76%
“…The RD/E dipeptide motif is similar to a phosphorylated RS domain, because the serine residue in the RS repeat is replaced with a negatively charged aspartic acid or glutamic acid residue. Consistent with this observation, the CF I m 68-kDa subunit was identified as a component of isolated IGCs (Saitoh et al, 2004).We previously reported that all three CF I m subunits (25, 59, and 68 kDa) are nuclear at steady state. Specific antibodies detect the proteins in the nucleoplasm and in discrete foci (Dettwiler et al, 2004).…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Many RNA processing factors, involved in either splicing or postsplicing processes such as mRNA export, nonsense-mediated decay, and polyadenylation, localize in speckles (16,(21)(22)(23)(24) and a speckled staining pattern indicates with near certainty a role in RNA processing (24)(25)(26). The virtually complete colocalization of bn2 with SC35 in nuclear speckles strongly suggests that bn2 has a function in RNA processing, and its unusual evolutionary stability implies that this function is essential.…”
Section: Discussionmentioning
confidence: 98%